An increase in educator expectations of student character growth during participation in a community of practice - Mucinskas, Daniel; Clark, Shelby; Barendsen, Lynn; Gardner, Howard (Frontiers in Education, 2025)
Character education is a priority for many schools and teachers, with several prominent frameworks concerning the philosophy and practice of character and virtues in the field of education. Educators are often prepared to teach character through training programs and professional development. Yet there has been less attention to the possible role of Communities of Practice (COPs) in fostering teacher effectiveness, particularly for the encouragement of character development in adolescents. In a study of a global community of practice, 80 primarily secondary school educators were responsible for implementing a set of at least twelve 45-min lesson plans. The lessons were focused on exploring the meaning of “good work” through the lenses of excellence, ethics, and engagement, with associated character strengths embedded within the curriculum. Educators rated their feelings about whether their students would develop each of the 24 VIA character strengths in a pre-, mid-, and post-survey. They also completed a post-survey rating scale about their experiences in the Community of Practice. Two multilevel models were run to analyze the relationship between these two factors. Results demonstrated that educators who rated their Community of Practice experience highly were also more likely to believe that their students were developing a blend of character strengths from the start. Furthermore, for some additional strengths, educator confidence in students’ development grew significantly over time in a positive association with higher Community of Practice ratings. The findings suggest that Communities of Practice may be an effective format to support educators in developing their confidence and teaching practices for character education.